Preparation method of functionalized SiO2 / aluminum silicate nanofiber composite membrane
By modifying and cross-linking polymerization of aluminum silicate nanofibers and SiO2 nanoparticles, functionalized SiO2/aluminum silicate nanofiber composite membrane was prepared, which solved the problem of difficulty in separation and adsorbing of single types of functional groups in nanopowder materials in applications, and achieved efficient adsorption and structural stability.
Patent Information
- Application Number
- CN202510310096.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-17
AI Technical Summary
Nanopowl materials are difficult to completely separate in practical applications, and there is a risk of agglomeration and leakage. The adsorption functional groups on the surface of the nanomaterial are single, which limits its efficient adsorption ability to heavy metal ions.
The aluminum silicate nanofiber and SiO2 nanoparticles were modified by aminosilane coupling agent, succinic chloride was grafted to form an acid chloride group, and then the modified ethylenediaminetetraacetic acid dianhydride was used as a crosslinking agent to conduct cross-linking polymerization reaction between the aluminium silicate nanofiber and the aluminium chloride SiO2 nanoparticles to prepare a functionalized SiO2/aluminium silicate nanofiber composite film.
It realizes efficient cross-linking and composite modification of nanomaterials, improves the structural stability of the composite film and the adsorption performance of heavy metal ions, and overcomes the problem that nanopowder materials are not easy to recover.
Smart Images

Figure CN119819276A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum silicate composite films, and in particular to a functionalized SiO 2 Preparation method of aluminum silicate nanofiber composite membrane. Background Art
[0002] Adsorption is a common method for treating heavy metal pollution. Its adsorption effect mainly depends on the selected adsorbent material. Nanomaterials have attracted much attention in the field of heavy metal adsorption due to their unique properties such as small size effect, quantum effect and large specific surface area. In particular, SiO 2 Nanoparticles have become an important heavy metal adsorption material due to a series of advantages such as high specific surface area, developed porosity, a variety of organic ligands, excellent chemical stability, and environmental friendliness. In addition, hydrated aluminum silicate nanofibers, as an emerging environmentally friendly nano-mineral fiber, have a unique mesoporous tubular structure, a large specific surface area, and a strong ion exchange capacity, which also makes it have broad application prospects in the field of heavy metal adsorption treatment of sewage. However, these nanopowder materials face two major challenges in practical applications. On the one hand, they are difficult to completely separate from the treatment system, and there are risks such as agglomeration and leakage, which not only weakens their adsorption performance, but also may cause secondary pollution to the environment. On the other hand, the adsorption functional groups on the surface of nanomaterials are usually relatively single in type and limited in content, which to a certain extent restricts their efficient adsorption capacity for heavy metal ions. These two problems have seriously affected the SiO 2 , hydrated aluminum silicate nanofibers and other nanomaterials in the field of water treatment. Summary of the invention
[0003] In view of the above-mentioned defects of the prior art, the present invention provides a functionalized SiO 2 / The preparation method of aluminum silicate nanofiber composite membrane achieves efficient adsorption of heavy metals and solves the problem of difficult recycling of nano powder materials.
[0004] The technical solution of the present invention is as follows: a functionalized SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: (1) Aminosilane coupling agent was used to couple aluminum silicate nanofibers and SiO 2 The nanoparticles were modified to obtain amino-modified aluminum silicate nanofibers and amino-modified SiO 2 Nanoparticles; (2) respectively on the amino-treated aluminum silicate nanofibers and the amino-treated SiO 2 The surface of the nanoparticles was grafted with succinyl chloride to obtain acyl chloride aluminum silicate nanofibers and acyl chloride SiO 2 Nanoparticles; (3) Dissolve ethylenediaminetetraacetic acid dianhydride in N , N -dimethylformamide, then add 2-amino-1,3-propanediol and the first acid binding agent to reflux at 120-135°C for 12-18h, add deionized water and ethyl acetate to extract after the reaction, and dry the obtained organic layer and distill under reduced pressure, and recrystallize the product with ethyl acetate to obtain an intermediate, the reaction formula is as follows: ; (4) Using the intermediate as a crosslinking agent and the acyl chloride group as a polymerization site, 2 The nanoparticles undergo cross-linking polymerization reaction, and then are filtered to form a membrane. After being fully washed and dried, the weight is no more than 15g / m 2 Functionalized SiO 2 / aluminum silicate nanofiber composite membrane.
[0005] Furthermore, the step (1) specifically comprises ultrasonically dispersing the aluminum silicate nanofibers in a mixture of ethanol and water, and then adding an aminosilane coupling agent for stirring reaction, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5); 2 The nanoparticles were ultrasonically dispersed in a mixture of ethanol and water, and then an aminosilane coupling agent was added for stirring reaction. 2 The mass ratio of the nanoparticles to the aminosilane coupling agent is 1:(0.1-0.5).
[0006] Furthermore, the stirring reaction in step (1) is carried out at 60-90° C. for 8-12 hours.
[0007] Furthermore, the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
[0008] Furthermore, the step (2) specifically comprises ultrasonically dispersing the aminated aluminum silicate nanofibers in ethyl acetate, then adding the second acid binding agent, and slowly dropping succinyl chloride under nitrogen protection, followed by stirring for reaction, wherein the mass ratio of the aminated aluminum silicate nanofibers, the second acid binding agent and succinyl chloride is 1:(1-2):(2-4); the aminated SiO 2 The nanoparticles were ultrasonically dispersed in ethyl acetate, and then a third acid-binding agent was added. Succinyl chloride was slowly added dropwise under nitrogen protection and stirred for reaction. The aminated SiO 2 The mass ratio of the nanoparticles, the third acid binding agent and succinyl chloride is 1:(1-2):(2-4), and the second acid binding agent and the third acid binding agent are preferably triethylamine.
[0009] Furthermore, the stirring reaction in step (2) is carried out under nitrogen protection at room temperature for 12 to 16 hours.
[0010] Furthermore, in step (3), the mass ratio of ethylenediaminetetraacetic acid dianhydride, 2-amino-1,3-propanediol and the first acid binding agent is 1: (0.8-1.2): (0.5-1), and the first acid binding agent is preferably pyridine. The intermediate contains more N atoms with lone pairs of electrons and is rich in hydroxyl groups.
[0011] Furthermore, the step (4) specifically comprises chlorinated aluminum silicate nanofibers and chlorinated SiO 2 Nanoparticles are ultrasonically dispersed in ethyl acetate, and then the prepared intermediate and the fourth acid binding agent are added to carry out a cross-linking reaction, wherein the acylated aluminum silicate nanofibers, acylated SiO 2 The mass ratio of the nanoparticles, the intermediate and the fourth acid-binding agent is 1:(0.5-1):(1-3):(1-2), and the fourth acid-binding agent is preferably triethylamine.
[0012] Furthermore, the cross-linking reaction in step (4) is carried out at 60-80° C. for 8-12 hours.
[0013] On the one hand, the present invention uses an amino coupling agent to couple aluminum silicate nanofibers and SiO 2 The nanoparticles are modified by amino modification, and then succinyl chloride is grafted on their surface, thereby introducing abundant acyl chloride groups on the surface of the nanomaterial; on the other hand, the present invention utilizes the reaction between amino groups and acid anhydrides, and uses 2-amino-1,3-propanediol to modify the crosslinking agent, ethylenediaminetetraacetic acid dianhydride, to obtain a new type of modified crosslinking agent with stronger functionality. The crosslinking agent not only contains more N atoms with lone pairs of electrons, but also contains abundant hydroxyl groups, which significantly improves its crosslinking effect and functionality. On this basis, the present invention uses modified aluminum silicate and SiO 2 The surface acyl chloride groups are used as polymerization sites. The modified crosslinking agent is used to form a crosslinked structure between aluminum silicate nanofibers and SiO 2 The nanoparticles achieve efficient cross-linking and composite modification. In this way, SiO with excellent structural stability can be prepared by simple vacuum filtration technology. 2 / Nanofiber composite membrane overcomes the problem of nanopowder materials being difficult to recycle. Moreover, using modified ethylenediaminetetraacetic acid dianhydride as a crosslinking agent can not only further improve the porosity of the material during the crosslinking process, but also introduce more N atoms, O atoms and ester groups with lone pair electrons that have excellent adsorption properties for heavy metal ions, thereby significantly improving the material's adsorption properties for heavy metal ions.
[0014] The advantages of the present invention compared with the prior art are: The present invention realizes the 2The fusion and synergistic enhancement of nanoparticles in adsorption performance. The prepared composite membrane not only integrates the excellent adsorption capacity of both, but also introduces many atoms and functional groups with excellent adsorption performance for heavy metal ions during the cross-linking reaction, further improving the pore structure of the material, thereby further greatly improving the adsorption capacity of the composite membrane for heavy metals.
[0015] In addition, the present invention significantly enhances the structural stability of the nanocomposite film through the dual modification strategy of compounding and cross-linking, overcomes the limitation that the traditional nanomaterial powder form is difficult to effectively recycle and reuse during the application process, and enables the composite film to be easily recycled and reused, greatly improving the practical value and economic benefits of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the infrared spectrum of the intermediate obtained in Example 1.
[0017] Figure 2 The following is the H NMR spectrum of the intermediate obtained in Example 1. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.
[0019] Example 1 A functionalized SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: (1) 1 g of aluminum silicate nanofibers were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.1 g of 3-aminopropyltrimethoxysilane was added. The temperature was raised to 60 °C and stirred for 12 h. After the reaction, the fibers were filtered, washed repeatedly with ethanol and deionized water, and dried to obtain amino-modified aluminum silicate nanofibers. 2 The nanoparticles were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.1 g of 3-aminopropyltrimethoxysilane was added, the temperature was raised to 60 °C, and the reaction was stirred for 12 h. After the reaction, the mixture was filtered, washed repeatedly with ethanol and deionized water, and dried to obtain the amino SiO 2 Nanoparticles.
[0020] (2) 1 g of amino-silicon aluminum silicate nanofibers were ultrasonically dispersed in ethyl acetate, and then 1 g of triethylamine was added, and 2 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred at room temperature under nitrogen protection for 12 h. After the reaction, the aluminum silicate nanofibers rich in acyl chloride were filtered, repeatedly washed with ethanol and deionized water, and dried. 2The nanoparticles were ultrasonically dispersed in ethyl acetate, and then 1 g of triethylamine was added, and 2 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred for 12 h at room temperature under nitrogen protection. After the reaction, it was filtered, repeatedly washed with ethanol and deionized water, and dried to obtain acyl chloride-rich SiO 2 Nanoparticles.
[0021] (3) Dissolve 1 g of ethylenediaminetetraacetic acid dianhydride in N , N -dimethylformamide, then add 0.8g of 2-amino-1,3-propanediol and 0.5g of pyridine, reflux the reaction system at 120°C for 18h, add deionized water and ethyl acetate for extraction after the reaction, add anhydrous sodium sulfate to the organic layer for drying, filter and take the filtrate for vacuum distillation, the product is recrystallized with ethyl acetate to obtain an intermediate containing more N atoms with lone pairs of electrons and rich in hydroxyl groups. The reaction formula is as follows: .
[0022] The infrared spectrum of the intermediate is shown in Figure 1 As shown in the figure, 3400cm -1 The strong peaks on the left and right are the vibration peaks of -OH, 2920 cm -1 ~2850 cm -1 The absorption peak at 1640 cm is the characteristic peak of CH in methylene. -1 The absorption peak at 1590cm is the vibration peak of C=O. -1 Nearby is the stretching vibration peak of CN in the imide ring. The H NMR spectrum of the intermediate is shown in Figure 2 shown.
[0023] (4) 1 g of acyl chloride-rich aluminum silicate nanofibers and 0.5 g of acyl chloride-rich SiO 2 Nanoparticles were ultrasonically dispersed in ethyl acetate, and then 1g of the intermediate and 1g of triethylamine were added. The reaction system was heated to 60°C and stirred for 12h. After cooling to room temperature, ethyl acetate was added to the reaction system to reach 2000mL. 31.4mL of the reaction solution was filtered and repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10cm and a gram weight of 5g / m 2 Functionalized SiO 2 / aluminum silicate nanofiber composite membrane.
[0024] The functionalized SiO prepared in Example 1 2 The adsorption performance test experiment of the aluminum silicate nanofiber composite membrane is as follows: Prepare 100 mL of an aqueous solution with a lead ion concentration of 100 mg / L (lead nitrate as a reagent) in a flask, adjust the solution pH to 7 with 0.1 M NaOH, and add the prepared functionalized SiO 2 / aluminum silicate nanofiber composite membrane, and then adsorbed for 3 hours in a constant temperature oscillator at 30°C and 200 rpm. After adsorption, the upper clear liquid was taken and the concentration of lead ions in the clear liquid was determined by ICP-OES. The adsorption amount of lead ions by the adsorbent material was calculated by the following formula ( Q , mg / g), and the results are listed in Table 1.
[0025] Q =( C 0 - C t ) V / M Q is the adsorption amount (mg / g); C 0 is the initial concentration of heavy metal ions (mg / L); C t is the concentration of heavy metal ions after adsorption (mg / L); V is the volume of the solution (L); M is the mass of the adsorbent (mg).
[0026] Example 2 A functionalized SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: (1) 1 g of aluminum silicate nanofibers were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.3 g of 3-aminopropyltrimethoxysilane was added. The temperature was raised to 75 °C and stirred for 10 h. After the reaction, the fibers were filtered, washed repeatedly with ethanol and deionized water, and dried to obtain amino-modified aluminum silicate nanofibers. 2 The nanoparticles were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.3 g of 3-aminopropyltrimethoxysilane was added, the temperature was raised to 75 °C, and the reaction was stirred for 10 h. After the reaction, the mixture was filtered, washed repeatedly with ethanol and deionized water, and dried to obtain the amino SiO 2 Nanoparticles.
[0027] (2) 1 g of amino-silicon aluminum silicate nanofibers were ultrasonically dispersed in ethyl acetate, and then 1.5 g of triethylamine was added, and 3 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred at room temperature under nitrogen protection for 14 h. After the reaction, the aluminum silicate nanofibers rich in acyl chloride were filtered, repeatedly washed with ethanol and deionized water, and dried to obtain acyl chloride-containing aluminum silicate nanofibers. 2The nanoparticles were ultrasonically dispersed in ethyl acetate, and then 1.5 g of triethylamine was added, and 3 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred for 14 h at room temperature under nitrogen protection. After the reaction, it was filtered, repeatedly washed with ethanol and deionized water, and dried to obtain acyl chloride-rich SiO 2 Nanoparticles.
[0028] (3) Dissolve 1 g of ethylenediaminetetraacetic anhydride in N , N -dimethylformamide, then add 1g of 2-amino-1,3-propanediol and 0.75g of pyridine, and reflux the reaction system at 130°C for 15h. After the reaction, add deionized water and ethyl acetate for extraction, and add anhydrous sodium sulfate to the organic layer for drying. After filtering, take the filtrate and perform vacuum distillation. The product is recrystallized from ethyl acetate to obtain an intermediate containing more N atoms with lone pairs of electrons and rich in hydroxyl groups.
[0029] (4) 1 g of acyl chloride-rich aluminum silicate nanofibers and 0.75 g of acyl chloride-rich SiO 2 Nanoparticles were ultrasonically dispersed in ethyl acetate, and then 2 g of the intermediate and 1.5 g of triethylamine were added. The reaction system was heated to 70 ° C, stirred for 10 h, and then cooled to room temperature. Ethyl acetate was added to the reaction system to reach 2000 mL. 41.9 mL of the reaction solution was filtered and repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 10 g / m 2 Functionalized SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0030] Example 3 A functionalized SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: (1) 1 g of aluminum silicate nanofibers were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.5 g of 3-aminopropyltrimethoxysilane was added. The temperature was raised to 90 °C and stirred for 8 h. After the reaction, the fibers were filtered, washed repeatedly with ethanol and deionized water, and dried to obtain amino-modified aluminum silicate nanofibers. 2 The nanoparticles were ultrasonically dispersed in a mixture of 95% ethanol and water, and then 0.5 g of 3-aminopropyltrimethoxysilane was added, the temperature was raised to 90 °C, and the reaction was stirred for 8 h. After the reaction, the mixture was filtered, washed repeatedly with ethanol and deionized water, and dried to obtain the amino SiO 2 Nanoparticles.
[0031] (2) 1 g of amino-silicon aluminum silicate nanofibers were ultrasonically dispersed in ethyl acetate, and then 2 g of triethylamine was added, and 4 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred at room temperature under nitrogen protection for 16 h. After the reaction, the aluminum silicate nanofibers rich in acyl chloride were filtered, repeatedly washed with ethanol and deionized water, and dried to obtain acyl chloride-containing aluminum silicate nanofibers. 2 The nanoparticles were ultrasonically dispersed in ethyl acetate, and then 2 g of triethylamine was added, and 4 g of succinyl chloride was slowly added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the reaction system was stirred for 16 h at room temperature under nitrogen protection. After the reaction, it was filtered, repeatedly washed with ethanol and deionized water, and dried to obtain acyl chloride-rich SiO 2 Nanoparticles.
[0032] (3) Dissolve 1 g of ethylenediaminetetraacetic anhydride in N , N -dimethylformamide, then add 1.2g of 2-amino-1,3-propanediol and 1g of pyridine, and reflux the reaction system at 130°C for 12h. After the reaction, add deionized water and ethyl acetate for extraction, and add anhydrous sodium sulfate to the organic layer for drying. After filtering, take the filtrate and perform vacuum distillation. The product is recrystallized from ethyl acetate to obtain an intermediate containing more N atoms with lone pairs of electrons and rich in hydroxyl groups.
[0033] (4) 1 g of acyl chloride-rich aluminum silicate nanofibers and 1 g of acyl chloride-rich SiO 2 Nanoparticles were ultrasonically dispersed in ethyl acetate, and then 3 g of the intermediate and 2 g of triethylamine were added. The reaction system was heated to 80 ° C, stirred for 8 h, and then cooled to room temperature. Ethyl acetate was added to the reaction system until it reached 2000 mL. 47.1 mL of the reaction solution was filtered and repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 15 g / m 2 Functionalized SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0034] Example 4 A functionalized SiO 2 The method for preparing a composite membrane of aluminum silicate nanofibers is as follows: Steps (1), (2) and (3) are the same as those in Example 1; Step (4) is to mix 1 g of aluminum silicate nanofibers rich in acyl chloride groups and 0.5 g of SiO 2Nanoparticles were ultrasonically dispersed in ethyl acetate, and then 1g of the intermediate and 1g of triethylamine were added. The reaction system was heated to 60°C and stirred for 12h. After cooling to room temperature, ethyl acetate was added to the reaction system to reach 2000mL. 62.8mL of the reaction solution was filtered and repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10cm and a gram weight of 10g / m 2 Functionalized SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0035] Example 5 A functionalized SiO 2 The method for preparing a composite membrane of aluminum silicate nanofibers is as follows: Steps (1), (2) and (3) are the same as those in Example 1; Step (4) is to mix 1 g of aluminum silicate nanofibers rich in acyl chloride groups and 0.5 g of SiO 2 Nanoparticles were ultrasonically dispersed in ethyl acetate, and then 1g of the intermediate and 1g of triethylamine were added. The reaction system was heated to 60°C and stirred for 12h. After cooling to room temperature, ethyl acetate was added to the reaction system to reach 2000mL. 94.2mL of the reaction solution was filtered and repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10cm and a gram weight of 15g / m 2 Functionalized SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0036] Comparative Example 1 A method for preparing an amino-modified aluminum silicate nanofiber membrane comprises the following steps: According to step (1) of Example 1, amino-modified aluminum silicate nanofibers were prepared, and then 1 g of amino-modified aluminum silicate nanofibers were dispersed in 2000 ml of ethyl acetate and dispersed evenly by ultrasonication. 78.5 ml of the dispersion was filtered to form a membrane, and the membrane was repeatedly washed with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 The adsorption performance of the amino-containing aluminum silicate nanofiber membrane was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0037] Comparative Example 2 Ammoniated SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: According to step (1) in Example 1, amino-aluminum silicate nanofibers and amino-SiO 2Nanoparticles, then 1g of amino-modified aluminum silicate nanofibers and 0.5g of amino-modified SiO 2 The nanoparticles were dispersed in 2000 mL of ethyl acetate and dispersed evenly by ultrasonication. 52.4 mL of the dispersion was filtered to form a membrane, and then washed repeatedly with deionized water. After drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 Amination of SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0038] Comparative Example 3 A cross-linked modified SiO 2 A method for preparing a composite membrane of aluminum silicate nanofibers comprises the following steps: According to step (1) in Example 1, amino-aluminum silicate nanofibers and amino-SiO 2 Nanoparticles, then 1g of amino-treated aluminum silicate nanofibers and 0.5g of amino-treated SiO 2 Ultrasonic dispersion of nanoparticles N , N -dimethylformamide, add 1g of ethylenediaminetetraacetic anhydride, and stir at 60℃ for 6 hours under nitrogen protection. After the reaction is completed, add N , N -dimethylformamide until the reaction system reaches 2000mL, take 31.4mL of the reaction solution for suction filtration, repeatedly wash with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 5g / m 2 Cross-linked modified SiO 2 The adsorption performance of the composite membrane of aluminum silicate nanofiber was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0039] Table 1 Adsorption amount of lead ions by the adsorption films prepared in Examples 1-3 and Comparative Examples 1-3
[0040] It can be seen from the above results that in the composite membrane prepared in the embodiment of the present invention, the aluminum silicate nanofibers and SiO 2An effective interface bond is formed between the nanoparticles, achieving a strong combination and synergistic effect in adsorption performance. At the same time, a rich amount of atoms and functional groups with excellent adsorption performance for heavy metal ions are introduced during the cross-linking process, and the cross-linking effect further improves the porosity of the composite membrane. These three advantages give the composite membrane excellent adsorption capacity for lead ions, and its adsorption capacity for lead ions can reach 339 mg / g. In contrast, the simply amino-treated aluminum silicate nanofibers in Comparative Example 1 cannot form an effective cross-linking structure, and lack of rich functional groups and SiO 2 The synergistic adsorption effect of SiO 2 The adsorption of aluminum silicate nanofibers and aluminum silicate nanofibers is weak, but the interface bonding between the two is weak, resulting in weak synergistic enhancement between the two, and the adsorption functional groups contained are single and relatively small in content; in Comparative Example 3, the cross-linking agent ethylenediaminetetraacetic acid dianhydride is not modified, so that fewer adsorption functional groups are introduced during the cross-linking reaction. Therefore, the adsorption materials prepared in these three comparative examples cannot compare with the functionalized SiO prepared in the embodiment in terms of the number of adsorption functional groups, the richness of the pore structure, and the strength of the synergistic adsorption. 2 / aluminum silicate nanofiber composite membranes, resulting in a significant decrease in their adsorption capacity for lead ions.
[0041] Furthermore, by comparing the adsorption results of Examples 1, 4, and 5, although increasing the mass of the membrane (mainly by increasing the thickness of the membrane rather than the diameter) can provide more adsorption sites, the increase in thickness slows down the diffusion rate of ions in the membrane, that is, the permeability decreases, which to a certain extent hinders the effective contact and adsorption of metal ions with the active sites. Therefore, when the thickness of the membrane reaches a certain threshold, the growth of the actual adsorption amount is no longer in line with expectations, and may even show a downward trend.
Claims
1. A method for preparing a functionalized SiO2 / aluminum silicate nanofiber composite membrane, characterized in that: The following steps are involved: (1) Aluminum silicate nanofibers and SiO2 nanoparticles are modified by aminosilane coupling agent to obtain amino-modified aluminum silicate nanofibers and amino-modified SiO2 nanoparticles, respectively; (2) grafting succinyl chloride onto the surfaces of the amino aluminum silicate nanofibers and the amino SiO2 nanoparticles, respectively, to obtain acyl chloride aluminum silicate nanofibers and acyl chloride SiO2 nanoparticles; (3) Dissolve ethylenediaminetetraacetic acid dianhydride in N , N -dimethylformamide, then add 2-amino-1,3-propanediol and the first acid binding agent to reflux at 120-135°C for 12-18h, add deionized water and ethyl acetate to extract after the reaction, and dry the obtained organic layer and distill under reduced pressure, and recrystallize the product with ethyl acetate to obtain an intermediate, the reaction formula is as follows: ; (4) using the intermediate as a crosslinking agent and the acyl chloride group as a polymerization site, a crosslinking polymerization reaction is carried out between the acyl chloride aluminum silicate nanofibers and the acyl chloride SiO2 nanoparticles, and then filtering to form a membrane, and after sufficient washing and drying, a film with a gram weight of no more than 15 g / m 2 Functionalized SiO2 / aluminum silicate nanofiber composite membrane.
2. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The step (1) specifically comprises ultrasonically dispersing aluminum silicate nanofibers in a mixture of ethanol and water, and then adding an aminosilane coupling agent for stirring reaction, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5); ultrasonically dispersing SiO2 nanoparticles in a mixture of ethanol and water, and then adding an aminosilane coupling agent for stirring reaction, wherein the mass ratio of the SiO2 nanoparticles to the aminosilane coupling agent is 1:(0.1-0.5).
3. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 2, characterized in that: The stirring reaction in step (1) is carried out at 60-90° C. for 8-12 hours.
4. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 2, characterized in that: The aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
5. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The step (2) specifically comprises ultrasonically dispersing the amino aluminum silicate nanofibers in ethyl acetate, then adding a second acid binding agent, and slowly dropping succinyl chloride under nitrogen protection, and then stirring the reaction, wherein the mass ratio of the amino aluminum silicate nanofibers, the second acid binding agent and succinyl chloride is 1:(1-2):(2-4); ultrasonically dispersing the amino SiO2 nanoparticles in ethyl acetate, then adding a third acid binding agent, and slowly dropping succinyl chloride under nitrogen protection, and then stirring the reaction, wherein the mass ratio of the amino SiO2 nanoparticles, the third acid binding agent and succinyl chloride is 1:(1-2):(2-4).
6. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 5, characterized in that: The stirring reaction in step (2) is carried out under nitrogen protection at room temperature for 12 to 16 hours.
7. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: In the step (3), the mass ratio of ethylenediaminetetraacetic acid dianhydride, 2-amino-1,3-propylene glycol and the first acid binding agent is 1: (0.8-1.2): (0.5-1).
8. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 1, characterized in that: The step (4) specifically comprises the following steps: ultrasonically dispersing the aluminum silicate nanofibers and the SiO2 nanoparticles in ethyl acetate, and then adding the prepared intermediate and the fourth acid binding agent to carry out a cross-linking reaction, wherein the mass ratio of the aluminum silicate nanofibers, the SiO2 nanoparticles, the intermediate and the fourth acid binding agent is 1:(0.5-1):(1-3):(1-2).
9. The method for preparing the functionalized SiO2 / aluminum silicate nanofiber composite membrane according to claim 8, characterized in that: The cross-linking reaction in step (4) is carried out at 60-80° C. for 8-12 hours.
Citation Information
Patent Citations
Hydrophilic flame-retardant modified polyimide fiber
CN113773492A
Nano-composite antibacterial non-woven fabric as well as preparation process and application thereof
CN114351440A
Preparation method and application method of HKUST-1 / silicon dioxide porous composite membrane
CN114699929A
Cited By
Water treatment filtering material and preparation method thereof
CN120618275A